Changes in Frequency and Patterns of Marital Sexual Activity During COVID-19: Evidence from Longitudinal Data Prior to, During and After Lockdown in Singapore. Issue 2 (12th December 2021) - Tan, Poh Lin
ABSTRACT: Background: The literature suggests that the pandemic has affected sexual activity and sexual desire around the world, potentially due to increased levels of stress, movement restrictions under lockdown conditions, and changes in relationship quality. Aim: To investigate changes in frequency and patterns of marital sexual activity and the role of potential factors underlying these changes, during and after COVID-19 lockdown. Methods: This longitudinal study followed 409 heterosexual married female participants who completed a baseline survey in April–July 2018 and biweekly online surveys over the next 14 weeks; an online survey in May 2020 during the lockdown in Singapore; and an online survey in June 2020 after the lockdown was lifted. Participants were recruited in 2018 using street intercept and screened for inclusion and exclusion criteria. Logistic fixed-effects models were used to test for changes in frequency and patterns of marital sexual activity and assess underlying factors. Pseudo-design-based sample weights were applied. Outcomes: The 2018 in-person baseline survey collected information on demographic characteristics and ideal frequency of marital sex, while follow-up online questionnaires in May–June 2020 included items on exact dates of marital sexual activity of previous weeks; stress and fatigue levels; both spouses' stay-at-home statuses during lockdown; and marital satisfaction. Results: 409 heterosexual married women were included in this study. Compared to pre-pandemic levels, the proportion of participants not having marital sex within a week remained stable while weekly sexual frequency increased, with more evenly distributed sexual activity on weekdays and weekends. Stress, fatigue, and marital satisfaction levels predicted probability of non-activity and sexual frequency. Clinical Translation: The increase in weekly sexual frequency has implications for sexual and reproductive health, including sexual satisfaction and prevalence of infertility and low birth weight associated with waiting time to pregnancy. Strengths & Limitations: The longitudinal nature of the dataset provides unique insights into differences in frequency of marital sexual activity during compared to before the pandemic. Unlike previous studies, detailed data on exact dates of sexual activity allow for detection of differences in sexual activity by day of the week. However, dates of sexual activity were recorded retrospectively and may contain recall errors. Data were collected only from wives and hence dates of marital sexual activities were not cross-validated with husbands. Conclusion: Results point to more active and flexible marital sex lives during the pandemic, with effects that persisted after the lockdown ended.